1990
DOI: 10.1001/archotol.1990.01870070084015
|View full text |Cite
|
Sign up to set email alerts
|

The Pressure Exerted by Mucoceles in the Frontal Sinus: An Experimental Study in the Cat

Abstract: The pathophysiologic process that results in bone erosion from frontal sinus mucoceles has long been a mystery. Traditionally, bone erosion has been attributed to pressure. However, no scientific evidence has yet been presented to support this hypothesis. To answer this question, seven cats had a mucocele created in one frontal sinus, with the other sinus left as a control. A manometer was inserted into each frontal sinus. Pressure readings were taken over a 7-month period. Pressures on the mucocele side were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…Frontal sinus osteomas and mucocoeles are associated in 16% of cases, however, only rarely is the pressure exerted by secretions sufficient to determine delayed erosion of sinus walls [12], meningeal layers and brain parenchyma, as we observed.…”
Section: Discussionsupporting
confidence: 46%
“…Frontal sinus osteomas and mucocoeles are associated in 16% of cases, however, only rarely is the pressure exerted by secretions sufficient to determine delayed erosion of sinus walls [12], meningeal layers and brain parenchyma, as we observed.…”
Section: Discussionsupporting
confidence: 46%
“…In case of the association of paranasal sinus mucocele and osteoma, osteoma is considered to cause the mucocele by occlusion of the sinus ostium. Fenton et al (9) induced mucocele formation in a feline model in experimental conditions. Maturo et al (10) demonstrated the frontal sinus mucocele formation in a goat model, induced by a long-term frontal recess obstruction by frontalis muscle plugging.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these conditions cause erosion of the frontal bone by stimulating osteoclastic action. 5,6 Small veins located under the basement membrane of the mucosa are valve less, penetrate the posterior wall of the sinus through vascular foramina, and gain access to the subdural space underlying the frontal lobes. This provides a clear avenue for the intracranial spread of infection to the subdural space.…”
Section: Introductionmentioning
confidence: 99%